Pengaruh Pemberian Berbagai Macam Jenis Alkohol Saat Marinasi Terhadap Nilai Organoleptik dan Tekstur Na’an Maran - Lehi Selfina Tamelab; Gemini Malelak; Geertruida Sipahelut (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of providing variouns types of alcoholicbeveranges on the Organoleptik value and texture of Na’an maran.The research method used is a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications so that there are 16 experimental units.The provision of various types of alcoholic beverages consists of P0 = 0%, P1= 10% beer, P2= 10% red wine and P3=10% sophia.The parameters measured in this study are colour, tenderness, level of preference, hardness, guminess, fracture, chewiness and cohesiveness and adhesiveness. The results of statistical analysis show that the addition of several types of alcoholic beverages has a very significant effect (P <0.01) on tenderness, level of preference, hardness, guminess, chewiness and a significant effect (P <0.05) on adhesiveness. But it has no significant effcet(P <0.05) on fracture and cohesiveness. Preference, hardness, guminess, chewiness and a significant effect (P <0.05) on adhesiveness. But it has no significant effcet (P <0.05) on fracture and cohesiveness.